Oxycodone vs. sufentanil combined with quadratus lumborum block vs. transverse abdominis plane block in laparoscopic major gastrointestinal surgery: A randomized factorial trial protocol - Guo-wang Yang; Min-yuan Zhuang; Hai-jing Shi; Xiao-yang Song; Hong Liu; Fu-hai Ji; Ke Peng (Heliyon, 2024)
Background: Multimodal analgesia plays a key role in enhanced recovery after surgery. Herein, we describe a trial protocol investigating the effects of oxycodone-vs. sufentanil-based patient-controlled analgesia in combination with quadratus lumborum block (QLB) vs. transverse abdominis plane block (TAPB) on quality of recovery following major laparoscopic gastrointestinal surgery. Methods: and analysis: This is a prospective, randomized, controlled clinical trial with a 2 × 2 factorial design. A total of 120 adult patients undergoing laparoscopic major gastrointestinal surgery will be randomized, in a 1:1:1:1 ratio, to receive one of two patient-controlled analgesia regimens (based on oxycodone or sufentanil) and one of two regional blocks (QLB or TAPB). The primary outcome measure of this trial is the quality of recovery at 24 h after surgery, assessed using the 15-item quality of recovery (QoR-15) scale. The secondary outcomes include QoR-15 scores at 48 and 72 h after surgery; visceral and incisional pain at rest and while coughing at 1, 6, 24 and 48 h postoperatively; analgesic consumption within 0–24 h and 24–48 h postoperatively; need for rescue analgesia; postoperative flatus time; postoperative adverse events (sedation, nausea and vomiting, use of antiemetics, respiratory depression, and dizziness); and length of postoperative hospital stay. Discussion: The results of this trial will provide evidence for the optimal multimodal analgesic strategy to improve the quality of recovery for patients undergoing laparoscopic major gastrointestinal surgery. Trial registration: This trial was registered at the Chinese Clinical Trial Registry (www.chictr.org.cn, identifier: ChiCTR2400080766).